Prediction of key toxicity endpoints of AP-238 a new psychoactive substance for clinical toxicology and forensic purposes using in silico methods - Kamil Jurowski; Alicja Krośniak (Scientific Reports)
Abstract This study performed advanced toxicological assessments of the new substance AP-238 using nine ‘green’ in silico methods, focusing on acute toxicity, organ-specific effects, skin and eye irritation, genetic toxicity, and cardiotoxicity. A quantitative assessment of AP-238’s acute toxicity (AT) was performed by predicting theoretical LD50 values for both rats and mice across different administration routes using various in silico methods. Results indicated the highest toxicity via intravenous administration in mice, with a t-LD50 of 53 mg/kg, while oral administration in rats exhibited a lower toxicity range, with t-LD50 values between 666.43 and 1838.77 mg/kg, depending on the predictive model used. The identification of toxicophores (the fragment connecting the benzene ring to the piperazine ring, including the α, β, and γ carbon atoms near the nitrogen atom) in AP-238 suggests a high likelihood of lung toxicity (61%), with additional risks to the cardiovascular (58%) and renal systems (56%), emphasizing specific molecular fragments associated with these adverse effects. Genotoxic evaluations presented a mixed view, with low to moderate probabilities of a positive Ames test, suggesting some uncertainty but generally indicating a reduced risk of genetic toxicity. Eye and skin irritation risks were deemed minimal, supported by several models with high confidence. Cardiotoxicity assessments revealed varied information on the potential effects of AP-238 on the hERG channel, with some studies suggesting a nonsignificant impact, while others indicated moderate risk, although with low reliability in the predictions. This highlights the nuanced challenges in assessing the safety of novel substances through ‘green’ in silico methods.